The impact of interest rates on the South African real estate market - Mahlangu, Nokuthula (My University, 2020)
Real estate not only represents a big part of individual and business investments, but also forms an important part of people’s livelihoods by providing shelter, alleviating poverty, and boosting income distribution. The real estate sector in South Africa is lagging in fulfilling this fundamental role. South Africa inherits most of its housing issues from an unpredictable economy and from the past and present governing and administrative systems. Housing and economic policies are intended to handle the housing backlog and issues which are a legacy of the period of inequality and segregation when access to housing and land was regulated based on race and ancestral tenure. To understand the dynamics in the residential real estate market better, this study sought to establish the impact of interest rates on the South African real estate market, using quarterly time series data from 1993Q2 to 2017Q4. Encompassed within the real estate market, this paper will focus on housing price indices and the market size which is represented by construction activity. These dependent variables are analysed against interest rates and moderated by inflation rates, gross domestic product (GDP), exchange rates, tax rates and the interaction term between interest rates and tax rates. A multiple linear regression model with OLS estimation method is used to determine the relationship between the variables. The dependent variables are evaluated individually against the explanatory variables. Overall, the obtained results show that interest rates have an indirect and significant relationship with housing prices; and a direct yet insignificant relationship with construction activity. As such, this suggests that interest rates are deemed adequate in explaining the movements in the house prices but not the movements in the entire real estate market. The insignificant relationship between interest rates and construction activity are surprising considering the theoretical and practical expectations. The results are largely attributed to shortcomings encompassed within the economy. Thus, it is believed that addressing the current economic shortfalls, along with additional research into the real estate market in South Africa should aid in both addressing problems and in further expanding the knowledge needed to effectively correct short falls within the economy and the real estate sector.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Finance and Investments to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2020
Keywords: Interest rates; Real estate market; South African real estate; UCTD; SDG-8: Decent work and economic growth